Análise dos argumentos persuasivos no gênero debate político televisionado - Silva, Romildo Barros da (2018)
This research presents a rhetorical-textual analysis of persuasive arguments in the televised political debate genre and is based on the theoretical assumptions of Aristotle (2011), Perelman and Tyteca (2014), Fiorin (2015) and Reboul (2004), highlighting the persuasive elements that are in textuality of the debate genre. In this genre, the debaters produce statement full of persuasiveness, generating controversial arguments that always indicate specific social functions. Persuasion is understood as a hidden phenomenon in the textual properties of political debate. This happens intentionally, since it has an effect when it is not perceived. In this sense, the political sphere takes advantage of this characteristic and produces discourses to involve the mass audience. With this activity, the political debate appears to be a genre conducive to discursive manipulation, but this is not verified or proven. Concerning this purpose, the attempts to persuade will be analyzed here, since, through types of arguments, places of argument and attacks on the opposing ethos, the debaters (rectors) make na undertaking to persuade part of the television audience. Rhetoric, in turn, is seen as the technique of persuading, captivating, and conquering the audience by discourse. However, persuasion is not a ready and finished product in speech, after all, a text can only be defined when it is socio-historically located. As far as rhetoric is concerned, the debate must be understood as an action of language that arises from a specific context and is also shaped by use. In addition to those already mentioned, this research brings theoretical contributions by Abreu (2009), Costa (2009), Marcuschi (2003, 2007, 2008 and 2010) among others. The corpus is made up of transcripts of a political debate of the second round of the 2014 presidential elections, televised by an open TV station. The analyzes point to the interrelationship between persuasive means and types of argument, since these argumentative categories together give persuasive effect to the statements of the debate genre. Of the types of argument analyzed it was noted that the almost logical, such as the argument of incompatibility, were recurrent in the discourse of the debaters and generally act to construct or deconstruct the projected image of the candidates. The place of quantity, the persuasive and hermeneutical functions and the projection of the ethos are also salient features in most of the debate. With this examination of the persuasive arguments, new theoretical assumptions about persuasion were gathered, as well as the possible applicability of rhetoric to texts. This, in a way, has contributed to reduce the theoretical scarcity with respect to the notion of analysis of the persuasive acts of the textual genres. Thus, this study is relevant for analyzing how the discursive phenomenon of persuasion in the televised political debate genre occurs, but also analyzes its arguments and characterizes its main social function: to persuade the universal audience.